Having Shed Illusions - Mowrer, Paul Scott (Tufts Archival Research Center, 2006)
Pulitzer Prize winning journalist and poet Paul Mowrer describes the importance of faith and hope to his beliefes, which include first hand experiences of both the good and bad that people can do.